IMPLEMENTASI SISTEM PAKAR BERBASIS WEBSITE UNTUK MENGIDENTIFIKASI HAMA TANAMAN PADI BESERTA PENANGANANNYA - Putri Taqwa Prasetyaningrum; Juwita Juwita (Jurnal Sistem Informasi dan Informatika (Simika), 2020)
The development of information technology is indispensable to help in the sharing of areas of life, one of which is in the field of agriculture. The use of information technology in agriculture can help a wide range of issues, especially the need to get information quickly. The farm is currently the largest community in Indonesia is rice that became staples in the country. Local rice production should be maximized by optimizing the farm itself, but problems in the cultivation of rice, one of the largest pest attacking the rice. Pest identification and handling shall be dealt with as quickly as possible in order not to experience a failed harvest.On this research designed an expert system for rice pest identification with method of bayes theorem and forward chaining to handle. The system is built to provide information on the pests of rice and penangananya on the basis of the symptoms that arise. The success of this research is 85%.